Molecular dynamics study on buckling of single-wall carbon nanotube-based intramolecular junctions and influence factors - Li, Ming; Kang, Zhan; Yang, Peiying; Meng, Xianhong; Lu, Yanjun (Computational materials science, 2013)
► We investigate strain rate effects on the buckling strain of CNT junctions. ► The deformation mode is different under high strain rate. ► We propose that failure mechanism at extreme high loading rate is wave propagation. ► We found temperature has a evident impact on compressive deformation. ► Buckling strains of junctions are lower than those of CNTs due to Stone–Wales defects. Carbon nanotube-based intramolecular junctions can function as rectifying diodes and switches in circuits and thus possesses the promising potential to be applied in nano-scale electronic devices. Due to their slender and unsymmetrical geometry, intramolecular junctions are prone to buckling under compression and the resulting structural instability will eventually leads to structural or electrical failure. Thus, it is important to explore the mechanical behaviors of intramolecular junctions subject to compressive loads. In this study, molecular dynamical simulations are carried out to investigate the compressive behaviors of intramolecular junctions at finite temperature, while carbon nanotubes are also studied as reference. The simulation results indicate that the strain rate effect is negligible within relatively low loading-rate range but the critical strain increases significantly under higher loading rate. At an extremely high strain rate, the intramolecular junctions will crush immediately. It is also predicted that local deformation will be introduced at high environmental temperature. Moreover, with increasing tube length, the instability mode of the intramolecular junctions transfers from shell buckling to column buckling and the critical aspect ratio is lower than that of carbon nanotubes due to presence of the Stone–Wales defects.